Catalytic Hydrogenation: Organometallic Synthesis of Bimetallic Cobalt‐Rhodium Nanoparticles in Supported Ionic Liquid Phases (CoxRh100−x@SILP) as Catalysts for the Selective Hydrogenation of Multifunctional Aromatic Substrates (Small 5/2021). Issue 5 (4th February 2021) - Rengshausen, Simon; Van Stappen, Casey; Levin, Natalia; Tricard, Simon; Luska, Kylie L.; DeBeer, Serena; Chaudret, Bruno; Bordet, Alexis; Leitner, Walter
Abstract : In article number 2006683, Alexis Bordet, Walter Leitner, and co‐workers present bimetallic cobalt‐rhodium nanoparticles of precisely controlled Co:Rh ratios synthesized on imidazolium‐based supported ionic liquid phases (Co x Rh100− x @SILP) following an organometallic approach. The resulting materials are characterized in detail, and their hydrogenation performances are investigated using multifunctional aromatic substrates as chemical probes. The Co:Rh ratio of the nanoparticles has a critical and synergistic influence on the activity and selectivity controlling in particular the ring hydrogenation of the aromatic moiety.